Older men in motion: bodies, masculinities, and redefinition of identity - González-Calvo, Gustavo; García-Monge, Alfonso; Ramalho, André; Hamdi, Faten; Duarte-Mendes, Pedro (Frontiers in Psychology, 2025)
IntroductionThis study explores the intersection of physical exercise, masculinity, and aging in older men, examining how these elements shape identity and bodily experiences. Aging is often framed through deficit-based narratives that emphasize decline; however, this research seeks to reframe aging as a process of adaptation and opportunity. By investigating how physical activity contributes to identity reconstruction, this study aims to provide insights into the broader social and structural factors influencing older men’s engagement in exercise.MethodsThe study employs a qualitative research design, utilizing semi-structured interviews with 12 men aged 65–76. A narrative thematic analysis was conducted to examine participants’ experiences, concerns, and expectations regarding physical activity. This approach allowed for an in-depth exploration of how exercise intersects with notions of masculinity and aging, as well as the barriers and facilitators that shape participation in physical activities.ResultsThe analysis identified three key themes: (1) the transformative role of exercise in fostering emotional well-being and bodily awareness, (2) the renegotiation of traditional masculinity through engagement in non-traditional physical activities, and (3) the social connections cultivated through group-based exercise programs. Additionally, the study highlights social and structural barriers, such as limited access to facilities and economic constraints, which hinder participation in physical activity.DiscussionFindings underscore the significance of physical activity not only for maintaining health but also as a space for identity reconstruction and resistance to conventional narratives of aging. The study suggests that exercise serves as a means of empowerment, allowing older men to navigate aging in ways that challenge societal expectations. Moreover, the identification of structural barriers emphasizes the need for inclusive public health policies and targeted interventions that promote active aging. By reframing aging as a dynamic process of adaptation rather than mere decline, this research contributes to a broader understanding of how older adults experience and engage with physical activity.